ANALISIS KEBIJAKAN DESENTRALISASI FISKAL TERHADAP KINERJA SEKTOR PERTANIAN DI PROPINSI BENGKULU - Rudi Hartono; Eko Priyotomo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2006)
Law No.32/2004 on Regional Government and Law No. 33/2004 in Intergovernmental Fiscal Relations are the basis of implementing fiscal decentralization, which may affecting the performance of regional economy. Objectives of research are to: (1) evaluate the implementation of fiscal decentralisation; (2) analyze factors affecting regional fiscal receipt and expenditure; (3) analyze factors affecting agriculture sector performance